2016
DOI: 10.1590/0103-8478cr20141800
|View full text |Cite
|
Sign up to set email alerts
|

Enzymatic activity in braúna seeds subjected to thermal stress

Abstract: To occur seed germination distinct hydrolytic enzymes work together, enabling primary root protrusion. The objective of this study was to investigate changes in the activities Palavras-chave:α-amilase, β-amilase, glicose-6-fosfato desidrogenase, Melanoxylon braúna.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 21 publications
0
2
0
Order By: Relevance
“…In seeds exposed to heat stress, glucose levels decreased been accompanied by a reduction in α and β-amylase enzyme activities. In M. brauna, heat stress also reduced the activity of α and β-amylase after a period of 48 h of imbibition (Ataíde et al, 2016). All these data show that the supply of sugars was affected after forest seeds (O. coarctata or M. brauna) to suffer heat stress.…”
Section: Discussionmentioning
confidence: 78%
See 1 more Smart Citation
“…In seeds exposed to heat stress, glucose levels decreased been accompanied by a reduction in α and β-amylase enzyme activities. In M. brauna, heat stress also reduced the activity of α and β-amylase after a period of 48 h of imbibition (Ataíde et al, 2016). All these data show that the supply of sugars was affected after forest seeds (O. coarctata or M. brauna) to suffer heat stress.…”
Section: Discussionmentioning
confidence: 78%
“…Studies have also shown that high temperature stress affects the activity of storage enzymes. In seeds of different species such as M.brauna, Erythrina velutina, and O. coarctata, the mobilization of reserves is impaired after heat stress (Ataíde et al, 2016;Felix et al, 2020;.…”
Section: Introductionmentioning
confidence: 99%